Effect of tamsulosin on ureteric stent related morbidity: a double-blind randomized placebo-controlled study - Singh, Ripudaman; Bhangu, Gurpreet Singh; Bansal, Darpan; Rattan, Anuj (International Surgery Journal, 2020)
Background: Post ureteral stenting, symptoms occurs of lower urinary tract which impact quality of life in around 80% of patients, urgency, frequency, dysuria, suprapubic pain, hematuria. α1-Adrenoceptors are found in highest density in the distal ureter. α1-Adrenoceptor antagonists dilates the lumen of the ureter and reduces the spasms by decreasing the peristaltic frequency and inhibiting basal tone of the ureter, leading to improvement in stent-related symptoms. This study was conducted to study effect of tamsulosin, a selective α1A- and α1D-adrenoceptor antagonist in relieving ureteric stent related symptoms Methods: A randomized double blinded placebo-controlled study conducted from February 2019 to August 2020 in Department of Surgery SGRD University, Amritsar. We enrolled 60 patients with each group of 30 patients (Group A placebo and Group B Tamsilosin 0.4 mg). IPSS (irritative and obstructive), quality of life (QoL) and visual analog scale VAS) pain score were calculated based on post-operative day one versus at Stent removal day (Post-operative day 21) at 3 weeks observations. analysis was done using Statistical package for social sciences (SPSS) version 23.0. Student ‘t’test (unpaired) and Chi-square test. Results: IPSS, QoL and VAS showed improvement with significant relieve of symptoms in patients on tamsulosin compared to placebo at time of stent removal. Conclusions: The study concluded that administration of tamsulosin a selective α1-blocker is useful in decreasing lower urinary tract symptoms in patients undergoing ureteral stenting.